A Antecedent Analysis Of Employee E-Hrm Effectiveness In Companies Implementing E-Hrm In Batam City - Farid, Ridhayati; Ella Triana Wirawan; Yuddy Giovanna Priscilla (Jurnal Manajemen dan Keuangan, 2025)
The use of "Electronic Human Resource Management" (E-HRM) helps companies become more efficient as a result of the fierce competition among them to recruit and retain professional staff. However, it was found that there was an issue that the adoption of this system was not uniform in various companies, which caused a gap in the effectiveness of its use. This study aims to analyze the relationship between antecedents, behavioral intentions, E-HRM use, and E-HRM effectiveness. The research method implemented was in the form of a qualitative method, by raising the population in the form of all HR who have used E-HRM in a company located in Batam City, by sampling through purposive sampling, to obtain a sample of 280. The results of the study highlight the importance of fostering an organizational environment that supports and ensures employee readiness to optimize E-HRM results. The results of the hypothesis test indicate that performance expectancy and effort expectancy have a significant positive effect on behavioral intention. Performance expectancy had a significant positive effect on E-HRM usage, but effort expectancy could not show a significant effect on E-HRM Usage. Directly, E-HRM Efficacy Level is influenced by variables such as Performance expectancy, behavioral intention, and E-HRM usage, but cannot be directly influenced by Effort Expectancy.